Avoiding and Correcting Complications in Perinasal Trauma - Frodel, John L. (Facial Plastic Surgery, 2012)
Injuries to the nose and perinasal region are common. Although the nasal fractures are commonly recognized and properly addressed, injuries to adjacent structures such as the orbit, medial canthus, and midface skeleton can be missed or misdiagnosed, leading to improper primary treatment and subsequent secondary deformities. In this discussion, three common injuries will be discussed, including nasomaxillary fractures, limited naso-orbital-ethmoid fractures, and severe central facial injuries with naso-orbital-ethmoid fractures. For instructional purposes, a case example of inadequate primary diagnosis and subsequent delayed or secondary management will be followed by a case example of proper initial diagnosis and proper primary management.
Keywords: nasomaxillary fractures; pseudotelecanthus; naso-orbital-ethmoid injuries